Urgensi Nilai dan Norma dalam Pembentukan Konstitusi Indonesia - Aundrea, Felizhia Ceccile; Damayanti, Annisa Indah; Aundrea, Felizhia Cecille (Indonesian Journal of Educational Technology, 2025)
The Constitution plays a strategic role in the life of the nation and the state because it is the legal basis that regulates the structure of the state, relations between institutions, and the rights and obligations of citizens. This article uses a qualitative approach based on literature studies to explain the values and norms in the Indonesian Constitution, especially in the 1945 Constitution of the Republic of Indonesia (1945 Constitution of the Republic of Indonesia). The study results show that the Indonesian constitution functions as a legal apparatus and contains ideological, historical, and sociological values that reflect the nation's personality, such as people's sovereignty, cooperation, deliberation, social justice, and respect for human rights. The process of forming and amending the 1945 Constitution shows the dynamic nature of the constitution that is adaptive to the changing times. The Indonesian Constitution does not fully adhere to the Western-style principle of separation of powers, but develops a model of power distribution based on the nation's culture. The constitutional awareness of the public needs to continue to be strengthened to maintain constitutional values and norms in the state's practice towards national ideals based on Pancasila.